Transshipment Hubs, Trade, and Supply Chains - Anh Do; Sharat Ganapati; Woan Foong Wong; Oren Ziv (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
The majority of global trade moves by sea through hub-and-spoke shipping networks. We investigate the returns to being a hub country by analyzing how transshipment activity shapes trade and supply chains. We show that most US imports especially from smaller origin countries are transshipped via key hubs, and transshipment is positively correlated with the hubs product-level trade. Leveraging the indirect shipping network structure to construct an instrument, we find that transshipment increases hubs imports from origins for which they facilitate trade and exports of downstream goods, highlighting their central role in shaping modern global trade and supply chain dynamics.
Keywords: F10; F13; F14; 330; trade costs; scale; hubs; transport costs; transportation networks; international trade; shipping